(3Pjd GdYHQs - (3TeS GdOjf CHi GdeMGSf eMeO Hf Ydj Hf GdMSf Hf MeRI GdMSjfj GdOeTbjs; (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3jHOC ef SfI (B741 s
(3BNQgG (B:s
(3jfJgi Edi SfI (B764 s
(3GdPi hUd ajg Edi SfI (B740 (3hHOC GdPjd ef SfI (B741 (3hGfJgi Edi SfI (B764s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B69 s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(1048) s
Keywords: (3GdJGQjNs